Aggressive systemic mastocytosis with diffuse bone marrow 18F-FDG uptake - Koukalová, Renata; Vašina, Jiří; Štika, Jiří; Doubek, Michael; Szturz, Petr (Nuklearmedizin - NuclearMedicine, 2021)
Mastocytosis is a clonal hematopoietic disorder characterized by proliferation of abnormal mast cells in various organs including the skin, digestive system, lymph nodes, and bone marrow. We report on a 75-year-old woman presenting with abdominal pain, vomiting, diarrhoea, myalgia, and weight loss. Abdominal CT showed hepatosplenomegaly with heterogeneous splenic parenchyma, lymphadenopathy, and osteopenia with areas of osteosclerosis but no primary tumour. An 18F-FDG PET/CT revealed an overall low metabolic activity of the lesions with a diffuse bone marrow involvement raising suspicion of a haematological neoplasm. Subsequently, bone marrow and peripheral blood examinations confirmed the diagnosis of aggressive systemic mastocytosis.
Keywords: Mastozytose; Positronen-Emissions-Tomografie; Computertomographie; KIT D816V Mutation; Osteopenie; Osteosklerose